Sustainable Transportation in the Context of Indonesia Emas 2045: Facilitating the Transition Towards an Environmentally Friendly Future - Annisa, Annisa; Sutanto, Sutanto; Arief, Budi; Wiradinata, Irvan (Universitas Batanghari Jambi, 2024)
Sustainable transportation plays a crucial role in realizing Indonesia's long-term vision for the year 2045, known as